Implementasi Algoritma Redundant Pattern Encoding Untuk Menyisipkan Pesan Teks Ke Dalam Gambar dan Algoritma Fibonacci Codes Untuk Kompresi - Frayogi Aditiya (Graha Mitra Edukasi, 2022)
Information is a collection of data in the form of unified text that is public or confidential. Confidential data is data that contains something or that is not for publication. One way to secure the data is to use Steganography techniques. This provides tremendous benefits for maintaining data confidentiality. In steganography there are several methods, one of which is Redundant Pattern Encoding. However, from this process, the object that will be used as a container to accommodate the data will experience a change in the size of the data. This can raise the suspicion of many parties who want to access the data. This study describes how the procedure is carried out to compress objects that are used as containers to insert messages. The process uses the Fibonacci Codes method which is a simple and very simple data compression method. The results of this research will produce a stronger level of data security.